The Development of Technology-supported Approaches to the LO Process for Accredited Engineering Programs - Dale Lackeyram; John R Donald; Richard Gorrie; Richard G Zytner (International Journal of Engineering Education, 2019)
Tracking graduate outcomes is a new requirement for engineering education in Canada.  Working closely with curriculum developers and educational technologists, the School of Engineering at the University of Guelph has shown it is possible to put in place an effective process.  The process requires engaged participants, an open-mindedness and integrated technologies to collect and report the data.  Combining people, process and technology provides a way for data analysis to satisfy accreditation requirements and internal quality education metrics.  This paper describes the approach taken and identifies strengths, challenges, and opportunities to be successful, and support the ultimate goal of curriculum improvement.